2011
DOI: 10.1111/j.1439-0272.2011.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic exposure to dimethoate and/or deltamethrin impairs sexual development and programs reproductive success in adult male offspring mice

Abstract: Pesticides can be toxic to desirable plants and animals, including humans. The aim of this study was to investigate the reproductive effects of low doses of pesticides on male offspring of exposed pregnant mice. Three groups of five female mice were treated daily by oral gavage with dimethoate (5 mg kg(-1) per day), deltamethrin (5 mg kg(-1) per day) and their mixture at 5 mg kg(-1) per day from day 3 to day 21 of pregnancy. Fertility, sexual behaviour and a number of reproductive endpoints, such as organ weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Decline in testicular weight might be due to the decline in serum testosterone levels (as obtained in our unpublished work). Our findings on reduced testicular weight also corroborates to that of earlier workers who observed a similar reduction in the weight of testis, epididymis, seminal vesicle and prostrate in Deltamethrin (EC) exposed Sprague Dawley rats for a period of 35 days 33,34,35 .…”
Section: Glycogensupporting
confidence: 92%
“…Decline in testicular weight might be due to the decline in serum testosterone levels (as obtained in our unpublished work). Our findings on reduced testicular weight also corroborates to that of earlier workers who observed a similar reduction in the weight of testis, epididymis, seminal vesicle and prostrate in Deltamethrin (EC) exposed Sprague Dawley rats for a period of 35 days 33,34,35 .…”
Section: Glycogensupporting
confidence: 92%
“…Pyrethroid‐induced male reproductive toxicity continues to be an active area of research because of the fact that the majority of the human population is exposed to these chemicals on a routine basis, that is, intake of the residual pyrethroids present in the food, use of insect repellents for household pest management and spraying on crops. Research reports in the last 5 years indicate that exposure to pyrethroids resulted in delayed Leydig cell development, [ 24 ] endocrine disruption, reproductive dysfunction, [ 25‐27 ] , and alterations in the epithelial and stromal cells of the prostate. [ 28 ] We demonstrated that exposure to allethrin caused reproductive dysfunction in male rats and disruption of expression of genes involved in germ cell production.…”
Section: Introductionmentioning
confidence: 99%
“…11 Delta has been shown to have adverse effects on male and female reproductive system. 12 In recent years, endocrine disruptors may be found in many products-including pesticides. These chemical products can block the signaling systems of hormones.…”
Section: Introductionmentioning
confidence: 99%